Sustainable by design - Render, Duanne A. (My University, 2010)
The increasingly rapid breakdown in natural systems that humankind is currently witness to has brought home the urgent need for a new approach to society. Modern technologies born of the Industrial and Information Ages have brought prosperity undreamt of by previous civilisations, but it is rapidly becoming clear that this prosperity may have come at too high a cost. This work will explore the issue of sustainability within the framework of architecture and the built environment, and attempt to identify a new paradigm for architectural design whereby built-environment professionals are able to ensure the consistent realization of sustainable architecture. The first part of the thesis will address the origins of and need for sustainability, and explore it within the context of architecture and the built environment. This will be followed by a critical investigation into conventional design practice and the emerging alternative - integrated design practice, and how suitable each of these design practices are for the task of ensuring sustainability. The second part of the thesis will detail a practical implementation of the conclusions reached in section one, investigating sustainable design in architecture using a “Design-Based Research” approach.